Immature Teratoma of the Submandibular Gland in a 3-Month-Old Infant: A Rare Case Report and Review of Literature - Hussain, Mohsina; Singh, Archana; Bendale, Kaustubh; Roy, Sirshendu; Gandhe, Sucheta; Pawar, Yogesh; Yasam, Ramesh Venkata; Nagarkar, Raj (Indian Journal of Medical and Paediatric Oncology, 2025)
Teratomas are embryonal neoplasms with the ability to develop in both gonadal and extragonadal sites. In this report, we present the case of an infant with a rare extragonadal site immature teratoma in the right submandibular gland. Although such cervical teratomas are a rare possibility, these should always be considered as a part of the differential diagnosis. Since these tumors can give rise to airway obstruction, early diagnosis and complete surgical resection of the tumor is the treatment of choice. Six months postoperatively, the infant is doing well with no evidence of disease with progressively decreasing alpha fetoprotein (AFP) values.
Keywords: immature teratoma; submandibular gland; infant; case report